Conflict Management Strategies in Ondo State Tertiary Institutions - Dorcas Oluremi Fareo; Mohamed Alison Jajua (European Scientific Journal, ESJ, 2018)
This paper investigated conflict management strategies in tertiary institutions in Ondo State. As a descriptive survey, the study population comprised all the staff and the management of three institutions. For the study sample, two hundred and ten was selected by stratified sampling technique. The instrument for data collection was 45 items Likert-type questionnaire tagged ‘Conflict Management Strategies Questionnaire’ (CMSQ). The reliability of the instrument was determined through test-retest method and the reliability co-efficient was 0.86. The content and face validity of the instrument was carried out by one expert in Test and Measurement, an expert in Psychology of Education; and an expert in Guidance and Counselling. The data collected were analyzed using frequency count, percentages, Analysis of Variance (ANOVA), and Multiple Regression. It was found that conflict in Federal University of Technology (FUTA), Rufus Giwa Polytechnic and Adeyemi College of Education occurred frequently. Nonpayment of salaries as at when due was the major cause of conflict in these institutions. The most effective conflict management strategies used was participatory decision strategy. Based on the findings, it was ascertained that role conflict occurred between academic staff and professional administrators; and conflict management strategies were critical variables in the school system. It was recommended that the academic and professional administrators should continue to demonstrate spirit of tolerance so as to ensure the smooth running of university, polytechnic and the college.